2022
DOI: 10.1097/pas.0000000000001928
|View full text |Cite
|
Sign up to set email alerts
|

“Malignant Mesenchymoma” Revisited

Abstract: Leiomyosarcoma (LMS) is the most common sarcoma in adults. Rarely, LMS dedifferentiates into an undifferentiated sarcoma. Very few cases of LMS with heterologous osteosarcomatous differentiation (OS) have been reported. The purpose of this study was to evaluate the clinicopathologic features of LMS with OS. Of 5570 LMS cases diagnosed from 2006 to 2022, 15 cases (0.2%) of LMS with OS were identified, affecting 13 females and 2 males; ages ranged from 32 to 66 years (median: 53 y). Ten tumors arose in the uteru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 29 publications
0
22
0
Order By: Relevance
“…In keeping with prior publications of dedifferentiated soft‐tissue LMS, 12 dedifferentiated uterine LMS was defined by two distinct components: One or more differentiated smooth muscle components, showing morphological features of smooth muscle differentiation, including fascicular architecture, abundant eosinophilic cytoplasm, and cigar‐shaped nuclei, or features characteristic of epithelioid or myxoid smooth muscle tumours, and immunophenotypic evidence of smooth muscle differentiation, defined as ≥5% tumour cells staining for smooth muscle actin (SMA), desmin, or caldesmon. A dedifferentiated component, without diagnostic smooth muscle morphology and with at most rare cells positive for any smooth muscle immunomarker. Heterologous differentiation was regarded as a form of dedifferentiation, in keeping with prior reports 13,16,22 …”
Section: Methodsmentioning
confidence: 62%
See 4 more Smart Citations
“…In keeping with prior publications of dedifferentiated soft‐tissue LMS, 12 dedifferentiated uterine LMS was defined by two distinct components: One or more differentiated smooth muscle components, showing morphological features of smooth muscle differentiation, including fascicular architecture, abundant eosinophilic cytoplasm, and cigar‐shaped nuclei, or features characteristic of epithelioid or myxoid smooth muscle tumours, and immunophenotypic evidence of smooth muscle differentiation, defined as ≥5% tumour cells staining for smooth muscle actin (SMA), desmin, or caldesmon. A dedifferentiated component, without diagnostic smooth muscle morphology and with at most rare cells positive for any smooth muscle immunomarker. Heterologous differentiation was regarded as a form of dedifferentiation, in keeping with prior reports 13,16,22 …”
Section: Methodsmentioning
confidence: 62%
“…Review of the literature identified 11 primary dedifferentiated uterine LMS. 12,[16][17][18][19][20][21] Follow-up was available in six cases, of whom three had died of disease at 4, 6, and 17 months, 16,17 one had died of other causes at 12 months, 12 and two were alive without disease at 12 and 28 months. 12,19 The literature also contains eight additional cases of primary conventional uterine LMS with subsequent dedifferentiation at metastatic sites, 16,21 with death from disease at median 7 months (range 1-18 months) after dedifferentiation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations